2022
DOI: 10.1155/2022/5239255
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Transcriptome Comparison of Brain and Kidney Endothelial Cells in Homeostasis

Abstract: Endothelial cells are heterogeneous, stemming from multiple organs, but there is still little known about the connection between the brain and kidney endothelial cells, especially in homeostasis. In this study, scRNA-seq results were obtained to compare genetic profiles and biological features of tissue-specific endothelial cells. On this basis, seven endothelial cell subpopulations were identified, two of which were upregulated genes in pathways related to stroke and/or depression, as characterized by neuroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Two predominant subsets of ECs in the brain, namely EC (Ptn) and EC (Col6a1), identified by their preferentially expressed genes, were juxtaposed with renal endothelial cells. These studies unveiled the positive role of three pathways in these subsets in the context of stroke and depression [16,18]. Furthermore, two genes -Ube2g1 and Pdcd4 -emerged as pivotal players in stroke development [16].…”
Section: Blood-brain Barrier Neurovascular Units and Endothelial Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…Two predominant subsets of ECs in the brain, namely EC (Ptn) and EC (Col6a1), identified by their preferentially expressed genes, were juxtaposed with renal endothelial cells. These studies unveiled the positive role of three pathways in these subsets in the context of stroke and depression [16,18]. Furthermore, two genes -Ube2g1 and Pdcd4 -emerged as pivotal players in stroke development [16].…”
Section: Blood-brain Barrier Neurovascular Units and Endothelial Cellsmentioning
confidence: 97%
“…Notably, understanding the varied genetic expressions of brain ECs in relation to ECs of other organs within the BBB context bears significant implications for future research endeavors. Previous investigations [16,17] have particularly cataloged the distinctive EC compositions within both the brain and kidneys. Two predominant subsets of ECs in the brain, namely EC (Ptn) and EC (Col6a1), identified by their preferentially expressed genes, were juxtaposed with renal endothelial cells.…”
Section: Blood-brain Barrier Neurovascular Units and Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%